Pengaruh Literasi Ekonomi Terhadap Hasil Belajar Siswa Kelas VIII pada Mata Pelajaran IPS di SMP Nurul Anwar Kota Bekasi - Ramdani Ramadhan; Nadia Rista; Sri Winarsih (Jurnal Ilmu Sosial dan Humaniora, 2025)
The purpose of this study was to determine the effect of economic literacy on the learning outcomes of eighth-grade students in social studies at Nurul Anwar Junior High School in Bekasi City. The data analysis technique used in this study was descriptive statistical analysis with simple linear regression. The results of the study concluded that economic literacy plays a significant role in supporting student achievement. The regression analysis yielded the equation Y = 70.270 + 0.130X. This equation indicates that every increase in economic literacy will be followed by an increase in learning outcomes of 0.130 points. Furthermore, economic literacy contributed 18.9% to learning outcomes, so although not the primary factor, economic literacy remains an aspect influencing student success. The t-test also supported this finding, where the calculated t-value (2.978) was greater than the t-table (2.024) with a p-value of 0.005. This means the null hypothesis is rejected and the alternative hypothesis is accepted. In other words, there is a significant relationship between economic literacy and student learning outcomes.